Sensitivity of banks towards macroeconomic and exchange rate / Nurul Wahidah Talib - Talib, Nurul Wahidah (2007)
This paper studied bank's sensitiveness to macroeconomic variables and exchange rate in Malaysia. Although some of the past studies of bank performance used usual macroeconomic explanatory variables, this was the first study to examine the impact of the exchange rate and macroeconomic variables on bank interest margins and profitability. This paper combining a broad cross section of bank balance sheet and income statement information in 5 local banks and 5 foreign banks in Malaysia with time series dimension (for the period 1996-2005). This paper had 3 dependent variables which are ROA (Return on Asset), ROE (Return on Equity) and NIM (Net Interest Margin) and 5 independent variables which were inflation, interest rate, economic growth, unemployment rate and exchange rate. Since there were several factors that affect the dependent variables, this paper used Multiple Linear Regression as a method for measuring the effects of several factors concurrently. The main conclusion of this paper was GDP was one of the macroeconomic variables that really affect bank profitability. However, some other independent variables also could contribute to the bank profitability.